An Eco-Theological Perspective on Oil and Gas Exploration in Papua, Indonesia - Mustaman Mustaman; Suparto Iribaram; Bambang Sunatar; Hasbullah Hasbullah; Abd. Rahman (FiTUA: JURNAL STUDI ISLAM, 2026)
This study examines oil and gas exploration and natural gas processing activities in the Sorong Raya region, Southwest Papua, Indonesia, particularly in Salawati Basin and Kasim Marine Terminal. The research explores how eco-theological perspectives derived from Islam, Christianity, and indigenous Papuan ecological values contribute to balancing environmental sustainability, economic welfare, and industrial development in one of Indonesia’s strategic energy regions. Previous studies on extractive industries in Papua have mainly emphasized political economy, environmental conflict, and resource governance, while limited attention has been given to ecotheology as an ethical framework integrating religious morality, indigenous ecological wisdom, and sustainable development. This study employed a qualitative phenomenological approach involving 15 participants, including indigenous Papuan communities, oil/gas workers, government officials, religious leaders, and civil society representatives. Data were collected through in-depth interviews, field observations, and document analysis. The findings show that the oil and gas sector contributes to regional income, employment, infrastructure, education, and local economic growth. However, respondents also identified environmental challenges, including marine pollution, ecological degradation, unequal economic distribution, and reduced customary access to natural resources. The study concludes that eco-theological and indigenous ecological values provide important ethical foundations for participatory, transparent, and culturally inclusive environmental governance in Sorong Raya.